Abdominal pressure pain thresholds correlate with postoperative pain intensity - Ghanad, Erfan; Weiß, Christel; Taebi, Niki; Klick, Jasmin; Staff, Sophie; Finze, Alida; Dusch, Martin; Reißfelder, Christoph; Schmelz, Martin; Yang, Cui (Science progress, 2025)
Objective - We aim to investigate the correlation between ongoing pain levels and pain threshold measured by algometry after bariatric surgery. - Methods - A retrospective analysis was conducted on data from 150 patients who underwent bariatric surgery, including 120 who received Roux-en-Y gastric bypass (RYGB) and 30 who underwent sleeve gastrectomy. Shortly after surgery, pain was assessed by the visual analogue scale (VAS) and abdominal algometry. Algometry was performed on the most sensitive abdominal pressure points. - Results - Patients reported moderate pain after surgery, with a mean of VAS score of 5.7. The mean abdominal pain threshold was 9.8N. VAS pain scores correlated with algometry (Spearman correlation coefficient −0.35; p < 0.0001). No sex-specific differences were observed in postoperative pain (p = 0.45) or algometry (p = 0.99). Furthermore, RYGB and sleeve gastrectomy groups did not differ significantly in the Spearman correlation coefficients (p = 0.214). - Conclusions - The mild correlation between reduced mechanical pain thresholds and higher levels of ongoing pain confirms the clinical value of sensory pain testing in the postoperative setting and suggests that local mechanical sensitization contributes to ongoing pain.